External influence of user's satisfaction of sport facilities at sport center of Matsushita Section 21, Shah Alam, Selangor / Muhamad Afiq Aziz - Aziz, Muhamad Afiq (Faculty of Education, 2014)
Healthy lifestyles have become a philosophy of life for a lot of people in the world. As a result, the number of who come to fitness centers dramatically increased. To be succeeding in this competition, service quality and client satisfaction viewed as a must by both academicians and practitioners. Nevertheless, the results of prior service properties that need to focus for the enhancement of the customer pleasure, is also an essential for mission of managers. The purpose of this study to find the external influence on satisfaction of sport facilities at sport centers of Matsushita Section 21, Shah Alam, Selangor. The respondents were 120 participants who are the people that attend to this sport center. A modified questionnaire from Wei Hung, Yang HC, Hsu, Ma (2010). The journal title is "Examination of the Influence of Service Quality on Membership Renewal in Fitness Centers in San Francisco Bay Area."It is to measure the facility factor (13 items), loyalty (6 items) and responsiveness (15 items) of the sport center. This study can be concluded majority respondents stated that they were excited to get involved in physical activities and this situation motivated them to go to Matsushita sport centre. The trust, believability and honesty that were offered by Matsushita sport centre encouraged respondents to make that particular sport center as their first choice. Moreover, they were willing to recommend Matsushita sport centre to others. Responsiveness and facilities were on second and third place respectively.